Constraining ultra light dark matter with the Galactic nuclear star cluster. Issue 2 (19th January 2022) - Toguz, Firat; Kawata, Daisuke; Seabroke, George; Read, Justin I
ABSTRACT: We use the Milky Way's nuclear star cluster (NSC) to test the existence of a dark matter 'soliton core', as predicted in ultra-light dark matter (ULDM) models. Since the soliton core size is proportional to m_DM^-1, while the core density grows as m_DM^2, the NSC (dominant stellar component within ∼3 pc) is sensitive to a specific window in the dark matter particle mass, m DM . We apply a spherical isotropic Jeans model to fit the NSC line-of-sight velocity dispersion data, assuming priors on the precisely measured Milky Way's supermassive black hole (SMBH) mass and the well-measured NSC density profile. We find that the current observational data reject the existence of a soliton core for a single ULDM particle with mass in the range 10 −20.4 eV ≲ m DM ≲ 10 −18.5 eV, assuming that the soliton core structure is not affected by the Milky Way's SMBH. We test our methodology on mock data, confirming that we are sensitive to the same range in ULDM mass as for the real data. Dynamical modelling of a larger region of the Galactic centre, including the nuclear stellar disc, promises tighter constraints over a broader range of m DM . We will consider this in future work.